2015
DOI: 10.1098/rspb.2015.1740
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife-friendly farming increases crop yield: evidence for ecological intensification

Abstract: Ecological intensification has been promoted as a means to achieve environmentally sustainable increases in crop yields by enhancing ecosystem functions that regulate and support production. There is, however, little direct evidence of yield benefits from ecological intensification on commercial farms growing globally important foodstuffs (grains, oilseeds and pulses). We replicated two treatments removing 3 or 8% of land at the field edge from production to create wildlife habitat in 50–60 ha patches over a 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
252
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(259 citation statements)
references
References 40 publications
6
252
0
1
Order By: Relevance
“…In fact, our results suggest that further investment in research into diversification techniques has the potential to improve productivity of sustainable agricultural methods to equal conventional yields. Encouragingly, the few long-term studies that have been conducted have demonstrated that diversification techniques enhance yields while enhancing ecosystem services, profitability and stability [18,23,[32][33][34][35].…”
mentioning
confidence: 99%
“…In fact, our results suggest that further investment in research into diversification techniques has the potential to improve productivity of sustainable agricultural methods to equal conventional yields. Encouragingly, the few long-term studies that have been conducted have demonstrated that diversification techniques enhance yields while enhancing ecosystem services, profitability and stability [18,23,[32][33][34][35].…”
mentioning
confidence: 99%
“…Pywall et al (2015) experimentally demonstrated for a 900 ha commercial arable farm in central England that wildlife-friendly management which supports ecosystem services is compatible with conventional crop yields. Their research suggests that in removing 3-8% of land from production at the field edge in order to create a wildlife habitat, there would be no adverse impact of this measure on overall yield in terms of monetary value or nutritional energy over a 5-year crop rotation.…”
Section: Population Recovery Option For Non-target Terrestrial Plantsmentioning
confidence: 99%
“…These methods represent a key element of 'ecological intensification' (Bommarco et al 2014;Pywell et al 2015), in which the role of functional biodiversity in delivering production-related ecosystem services such as pollination, soil fertility, water quality and pest regulation is actively managed and enhanced. Enhancing natural pest regulation can enable incremental reductions in the use of synthetic chemicals in crop and livestock protection.…”
Section: Systemaɵc Reviewmentioning
confidence: 99%